Occurrence and fate of organic micropollutants (OMPs) in Lake Mälaren - Rehrl, Anna-Lena (2019)
The main objective of this study is to investigate the occurrence and fate of organic micropollutants (OMPs) in surface water in Lake Mälaren over one year, including their seasonal variations, correlations between compounds, spatial and vertical distribution. The water samples were enriched with solid phase extraction (SPE) and subsequently analyzed by ultra-high pressure liq-uid chromatography tandem mass spectrometry (UPLC-MS/MS). The applied multi-residue method, consisting of OMPs with a wide range of physico-chemical properties was earlier optimized and then assessed regarding its per-formance. From 122 tested target compounds, 74 obtained a good relative re-covery (60-145%) and 50 were detected at least once above limit of quantifica-tion (LOQ), which ranged from 0.010 and 10 ng/L. The highest detected con-centration was found for valproic acid (2600 ng/L) and lamotrigine (140 ng/L). The locations Ekoln and Västeråsfjärden were identified to be most affected by OMPs pollution. Seasonal patterns were observed for numerous OMPs and 7 compounds occurred without seasonal fluctuations. Only a few vertical distri-bution patterns and concentration gradients were observed, for instance, the deepest sampling depth (30m) from Ekoln showed considerable higher concen-trations than the upper sampling depths in February. A strong positive correla-tion was found for carbamazepine and lamotrigine, but also for other OMPs. Two industrial chemicals, tolyltriazole and tris(2-butoxylethyl)phosphate showed very good analytical performance parameters and were detected fre-quently and it is recommended to incorporate these compounds more regularly in future analysis. No correlations between water chemistry were observed. To the best of our knowledge, this study is the first one to report the occurrence and distribution of OMPs representing such wide physico-chemical properties, including industrial chemicals, in a Swedish lake.